Tindak Tutur Ekspresif Dalam Kolom Komentar Youtube Kok Bisa? Mengenai “Seberapa Bahaya Vape Sebenarnya?” - Sukesih, Sri; Ningsih, Rika (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2026)
The objective of this study is to identify the expressive speech acts used in the comment section of the "Kok Bisa?" YouTube channel, specifically in the episode titled "Seberapa Bahaya Vape Sebenarnya?" (How Dangerous is Vaping, Really?). This study employs the content analysis method, chosen to identify the specific characteristics of a message objectively, systematically, and generally. Content analysis is utilized to analyze documents or existing written materials. The results of this study identified 20 data points categorized as expressive speech acts, consisting of 2 utterances of thanking, 5 utterances of praising, 5 utterances of complaining, 1 utterance of blaming, and 7 utterances of criticizing. The most dominant expressive speech act found was criticizing, with 7 data points. This occurred because the video upload on the "Kok Bisa?" YouTube account discussed the dangers of vaping, whereas vaping is often perceived as being safer than cigarettes. Consequently, many viewers commented by criticizing those who use vapes or similar products like cigarettes.